Strategy for Development of student,s ethics under of The Prachuap Khiri Khan Primary Educational Service Area Office 2 - Panmujcha, Nukul; Chotientip, Tassanee; Maneephruek, Wirat (Journal for Developing the Social and Community, 2021)
The purposes of this research were to study current conditions desirable conditions and requirements strategy for development of student,s ethics under of The Prachuap Khiri Khan Primary Educational Service Area Office 2. The sample was used in this study ;27 administrators, 280 teacher, and chairman of the basic education institution 27, a total of 334 persons. The instrument for data collection was 5-level rating scale questionnaire with IOC value between 0.85-1.00, and overall validity value of 0.98. The research findings were as follows : 1. current conditions desirable conditions and requirements strategy for development of student,s ethics under of The Prachuap Khiri Khan Primary Educational Service Area Office 2. The overall level is moderate. The highest average ;Development by setting up a school environment, Developed using good examples, Developed by student development activities, Development by teaching and learning and Development by community involvement.Desirable condition overall level is very high.The highest average ; development of teaching and learning, developed by student development activities, developed using good examples, development by community involvement and development by setting up a school environment. 2. Strategy for Development of student,s ethics under of The Prachuap Khiri Khan Primary Educational Service Area Office 2 ; strategy 1 : Development by teaching and learning 6 measure ; strategy 2 : Developed by student development activities 4 measure; strategy 3 : Developed using good examples 3 measure ; strategy 4 : Development by setting up a school environment 5 measure ; strategy 5 : development by community involvement 2 measure.